A STUDY OF HADOOP ECOSYSTEM - Ms.Prachi Dhaulakhandi (International Journal of Research Science and Management, 2016)
Hadoop rose around 10 years ago with the aim to improve Yahoo’s search engine. Hadoop was created by Doug Cutting and Mike Cafarella and was named after a toy elephant belonging to Doug Cutting’s son. Also Hadoop has its origin in Apache Nutch, an open source web search engine.